Hadith #334 - Sahih al-Bukhari - Abdur Rahman bin Abza (Sahih al-Bukhari)
A man came to `Umar bin Al-Khattab and said, “I became Junub but no water was available.” `Ammar bin Yasir said to `Umar, “Do you remember that you and I (became Junub while both of us) were together on a journey and you didn’t pray but I rolled myself on the ground and prayed? I informed the Prophet (ﷺ) about it and he said, ‘It would have been sufficient for you to do like this.’ The Prophet then stroked lightly the earth with his hands and then blew off the dust and passed his h
Grade: Sahih

Hadith #336 - Sahih al-Bukhari - Abdur Rahman bin Abza (Sahih al-Bukhari)
that while he was in the company of `Umar, `Ammar said to `Umar, “We were in a detachment and became Junub and I blew the dust off my hands (performed the rolling over the earth and prayed.)”
Grade: Sahih

Hadith #337 - Sahih al-Bukhari - Abdur Rahman bin Abza (Sahih al-Bukhari)
`Ammar said to `Umar “I rolled myself in the dust and came to the Prophet (ﷺ) who said, ‘Passing dusted hands over the face and the backs of the hands is sufficient for you.’ “
Grade: Sahih